Is Thomas Tuchel wrong? Evaluation of hexagonal shaped drills based on machine learning and position data - Paul, Y.; Mathes, J.; Brinkjans, D.; Maurus, E.; Memmert, D. (International Journal of Sports Science & Coaching, 2024)
As a variation of small-sided games (SSGs), Thomas Tuchel's hexagonal shaped possession drills attracted a lot of attention in coaches` soccer education. Changing certain variables (e.g. pitch size) is one traditional approach to provide an optimal stimulus for a specific training goal. Therefore, the presented field study investigated whether hexagonal shaped drills show changes in tactical key performance indicators (KPIs) using positional data in a controlled experimental setting. Data were collected using player tracking systems (1 Hz) in 5 versus 5 SSGs in both the full-size pitch and pitch with cut-off corners condition. At match-related level, trial duration and outcome were examined. At player-related level, the tactical KPIs effective playing space (EPS), length-per-width ratio, space control and overplayed defenders were analyzed. The results show significant differences in length-per-width ratio (attacking team), the EPS and space control (30m-zone). However, it could not be confirmed that hexagonal shaped drills are played more vertically and faster toward the goal than on a normal pitch, as there were no changes in trial duration, outcome or overplayed defenders. Nevertheless, an experimental positional data analysis paradigm is a useful approach to investigate tactical principles in high-level professional soccer.